2013
DOI: 10.1111/1365-2664.12143
|View full text |Cite
|
Sign up to set email alerts
|

Home range and resource selection by animals constrained by linear habitat features: an example ofBlakiston's fish owl

Abstract: Summary1. Typically in resource selection studies, the spatial extent of a home range is defined first and then the available resources within that perimeter are estimated. However, the home ranges (or habitats) of some animals are constrained by linear environmental features (e.g. rivers, shorelines). Traditional home range estimators often overestimate home range extent for such species, which can lead to spurious estimation of resource availability and selection. 2. We used a synoptic model of space use to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…However, obtaining constrained home range estimates remains difficult (e.g., Slaght et al, 2013). We found that the movements of the water opossum are constrained to river channels and banks.…”
Section: Home Range Sizementioning
confidence: 78%
See 4 more Smart Citations
“…However, obtaining constrained home range estimates remains difficult (e.g., Slaght et al, 2013). We found that the movements of the water opossum are constrained to river channels and banks.…”
Section: Home Range Sizementioning
confidence: 78%
“…Most home range estimators overestimate home range size for animals constrained to linear habitats because they include large unused areas (Sauer, BenDavid & Bowyer, 1999;Blundell, Maier & Debevec, 2001;Slaght et al, 2013). Therefore, we modelled and estimated the home range size for the water opossum in three different ways.…”
Section: Home Range Estimatorsmentioning
confidence: 99%
See 3 more Smart Citations